Intellectual Colonialism or Liberatory Education? An Exploration of Adult Education in an International Context - Ann Harris; Helen MF Jones (Adult Education Research Conference, 2004)
We examine colonialism through pedagogy, method, curriculum and knowledge and conclude by identifying potential for developing and developed countries to collaborate in knowledge creation. As a case study, we draw on the Commonwealth Youth Programme’s Diploma in Youth in Development. Does it deliver liberatory education or intellectual colonialism?